(untitled) - IRRI (Manila, 1998)
This update contains the latest publications on rice acquired by the IRRI library and documentation services. It also contains references published earlier and which were not included previously. The arrangement is classified by broad suject headings. All items included in the Update are available at the IRRI Library and Documentation Service. Photocopies of orginal documents ( not to exeed 50 pages ) are supplied free to readers in developing countries.Internet: c.austria@cgiar.org; WWW: http://ricelib.irri.cgiar.org.
Keywords: rice - bibliography